An assessment of sustainable energy access in rural households : a case of Kavrepalanchowk District, Nepal - Niraula, Pragya; Dhakal, Shobhakar; Kumar, Sivanappan; Salam, Abdul P.; Asian Development Bank-Japan Scholarship Program(ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2016)
72% of rural populations in Nepal are estimated to have access to electricity and 90% of rural populations still depend on traditional biomass for cooking. Nepal has opted for the UN initiative for Sustainable Energy for All since August 2012, which has one of its objectives to provide universal energy access by 2030. To reach into the required target, understanding the energy consumption pattern and identify sustainable access to clean and affordable energy services is essential. Therefore, the main objective of this study is to identify status of energy access and sustainable resource options to satisfy basic energy services in rural households. The study and its findings are mainly based on a household survey taken in one of the rural VDC in Kavrepalanchowk District of Nepal named as Pokhari Chauri. This dissertation presents the energy access scenario of rural households from four different perspectives namely energy poverty, energy demand, renewable energy resource and cost assessment. It was found that over 90% of sample households are in Tier 2 level (within the range of 67-321kWh/HH/year) in terms of electricity access and over 70% of the sample households are in Tier 0 (using traditional cook stoves) in terms of cooking access. The minimum threshold level of basic energy services in Pokhari Chauriwas found to be 135kWh/HH/year. The current and future electricity demand under BAU case and Energy Access program was estimated for Pokhari Chauri households. It was found that energy poor households could not meet GTF{u2019}s minimum threshold level (250kWh/HH/yr) by 2030 under BAU case while under EA program energy poor households could reach 254kWh/HH/yr. The energy non-poor population would reach the GTF threshold level of electricity consumption by 2021 under BAU case while under EA goals; energy non-poor households will use almost 606kWh/HH/year. Solar resources, agricultural residue and hydro power were determined as feasible energy resources for electricity generation in Pokhari Chauri. To meet the load demand of both energy poor households and energy non poor households, different scenarios are created. The simulation result showed that the micro hydro plant was able to meet the energy demand of rural households in all the scenarios based on low NPV and low COE. The least cost of electricity varies from 0.101 to 0.237$/kWh depending upon loads under different scenarios. In order to meet the peak load demand in some scenarios, batteries and converter are also considered for optimal design. The study have built a better understanding of how various interventions can improve access by considering various attributes of energy supply. In our case, the generation project must focus for longer hours of electricity supply, improvement on unscheduled electricity supply, adequate voltage supply. Likewise, for cooking access national scale program can be launched to introduce advance biomass cookstoves with proper training and awareness for using it that would move households from lower to the middle tiers. Improvement of existing micro hydro with proper infrastructure and the use of efficient machinery are suggested through this study to meet the current and the future electricity demand of households in Pokhari Chauri.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy
Thesis (M.Eng.) - Asian Institute of Technology, 2016
Keywords: Renewable energy sources -- Nepal; Sustainable energy -- Nepal